2012
DOI: 10.1001/archpediatrics.2011.716
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Performance at School

Abstract: Study Selection: We screened the titles and abstracts for eligibility, rated the methodological quality of the studies, and extracted data. Main Exposure: Studies had to report at least 1 physical activity or physical fitness measurement during childhood or adolescence. Main Outcome Measures: Studies had to report at least 1 academic performance or cognition measure during childhood or adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
2
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(196 citation statements)
references
References 30 publications
12
176
2
6
Order By: Relevance
“…The overall effect size across all decades of studies was .383. Other researchers conducting comprehensive reviews have reported similar findings (Biddle & Assare, 2011;CDC, 2010;Donnelly et al, 2009;Singh, et al, 2012;Trudeau & Shepard, 2008).…”
Section: Introductionmentioning
confidence: 58%
“…The overall effect size across all decades of studies was .383. Other researchers conducting comprehensive reviews have reported similar findings (Biddle & Assare, 2011;CDC, 2010;Donnelly et al, 2009;Singh, et al, 2012;Trudeau & Shepard, 2008).…”
Section: Introductionmentioning
confidence: 58%
“…A mérsékelten erőteljes fizikai aktivitás előnyösen hat a serdülők fizikai, szellemi és pszicho-szociális egészségére, mivel segíti az egészséges csontok és izmok építését és fenntartását, csökkenti a depresszió és a szorongás érzését (JANSSEN és LEBLANC, 2010;SINGH et al, 2012).…”
Section: Fizikai Aktivitás Szerepe Az Egészség Megőrzésében -Role Of unclassified
“…For the good predictive accuracy there were few researches which used decision tree algorithms and data mining [8], [1] and [15]. The impact of extracurricular activities to the student studies performance were vital to making an own method to calculate extracurricular performance according to the most effective factors in this implemented system [5] and [9].…”
Section: Research Gapmentioning
confidence: 99%